Breast Diseases in Children and Adolescents - A Two Year Experience in a Private Hospital of Dhaka (Journal of Paediatric Surgeons of Bangladesh, 2013)
Aim and objectives: The aim of this study was to evaluate the spectrum of breast diseases in the children and adolescents in a single hospital and to evaluate the presentation and outcome of these diseases. Methods: This prospective study of childhood and adolescents (2-19years) breast diseases conducted on 47 patients over a period from January 2009 to December 2011. A total of 47 (forty seven) children and adolescents (